Comparing farm and village-level determinants of millet diversity in marginal environments of India: the context of seed systems - Nagarajan, Latha; Smale, Melinda; Glewwe, Paul (International Food Policy Research Institute, 2005)
The purpose of the research paper is to characterize biological diversity related to millets in the semi-arid regions of India at various spatial scales of analysis (e.g., farm household versus community levels) and place that evidence in a broader seed systems (includes both formal and informal) context. An important finding of this research is that producer access to millet genetic resources is affected by the extent to which seed is traded via formal markets or through other social institutions, along with farm and household characteristics. Findings also underscore the need for an enhanced theoretical understanding of local seed markets in analyzing crop variety choices and the diversity of materials grown in less favored environments.